Efektivitas Penggunaan Software Pembelajaran Daring Dimasa Pandemi Covid-19 pada Guru SD Negeri 2 Abiansemal - I Gusti Ayu Agung Sinta Diarini; I Made Ari Winangun (Jayapangus Press, 2022)
Most of the teachers at SD Negeri 2 Abiansemal have not been able to carry out online learning to the fullest during the Covid-19 pandemic. This causes the learning process to run monotonously. Therefore, efforts are needed to maximize the ability of teachers to use online learning software. This effort was carried out in the form of research that aims to analyze the effectiveness of using online learning software during the Covid-19 pandemic for teachers at SD Negeri 2 Abiansemal. This research is a pre-experimental design with a one-group pretest-posttest design model. The population and sample of this study were all 16 teachers at SD Negeri 2 Abiansemal. The instrument used is the SAMR model test. Data analysis in this study was paired t-test as a difference test and N-gain as an effectiveness test. The results of this study indicate that the use of online learning software during the Covid-19 pandemic for teachers at SD Negeri 2 Abiansemal is effective in improving teaching abilities. (pretest < posttest = 64.06 < 92.19; tcount > ttable = 25,422 > 2,131; sig.(2-tailed) < α; N-gain = 79,98%).